A Study of Gain Improvement of a Slot Antenna Using Curved Metallic Holes Structure - Aitthiphak Boonyakiat (2020)
© 2020 IEEE. Nowadays, a microstrip slot antenna is widely used in the modern wireless communication systems because it has more advantages such as compact, easy fabrication, low cost, and wide bandwidth. However, it also has the drawback such low gain, because of its resonant nature of microstrip. Therefore, this paper presents a method to increase and improve the gain of slot antenna, a bandwidth of 1,800 MHz to 6,000 MHz, to apply for a modern wireless communication system. The new technique of metamaterial utilized for improving the gain of slot antenna is presented. From this study, the proper metamaterial, the curved metallic holes structure, is competent to improve the performance of slot antenna by increasing it directivity, gain, and radiation efficiency. Moreover, a behavior of gain characteristic, reflection coefficient (S11), and radiation pattern of slot antenna with and without a metallic holes structure are examined in this paper. From simulated results by simulation software, it noted that the gains of all the operating frequencies of a slot antenna with a metallic holes structure have been increased around 1.7 dB of all operating frequencies when compared to a slot antenna without a metallic holes structure.